Marketing and social media a guide for libraries, archives, and museums - Koontz, Christie; Mon, Lorri (Rowman & Littlefield, 2014)
Marketing and Social Media: A Guide for Libraries, Archives, and Museums is a guide to marketing for libraries, archives, and museum professionals in the social media age. This book is both an introductory textbook and a guide for working professionals who want to go beyond mere promotion to developing a planned and deliberately managed marketing campaign. Beginning with mission, goals, and objectives, readers will review the components of both the internal and external environments which must be understood to plan an objective campaign. Chapter coverage includes how to do a SWOT analysis, identify and involve stakeholders, a 4-step marketing model, market research, market segmentation, market mix strategy, and evaluation are all covered. Each chapter includes explanatory topical content designed to build a framework of marketing and social media management understanding including discussion questions (which can be developed into classroom or workshop assignments and key terms. Illustrative and brief case study examples from all three institution types are embedded in chapters as relevant.